Analysis of the Philosophical and Spiritual Meaning of Sidakarya Mask Dance - I.B. Gede Putra Kinandana (Bali Tourism Journal, 2024)
The Sidakarya mask is particularly important, symbolizing the descent of Wisnu Murti (Lord Vishnu) to conclude ceremonies. It belongs to the wali dance category and is typically performed close to the ceremony location, serving as a ceremonial conduit alongside the Ida Pedanda leads the prayer. This dance signifies the culmination of the offering ritual preceding the communal worship led by the Sulinggih. Consequently, the Sidakarya mask holds various theological, aesthetic, and philosophical meanings. the Sidakarya mask dance symbolizes the bestowal of prosperity, the elimination of all impurities and illnesses in oneself and nature (Bhuana Alit and Bhuana Agung). The Sidakarya mask dance is a figure of a Brahmana who has rendered service and is capable of creating prosperity for the Hindu community in Bali through the stories performed, which contain meanings and symbols of communication believed by Hindus as a sacred dance used to facilitate the conduct of yadnya ceremonies. The ngayab movement in the Sidakarya mask dance is a symbol of communication that ensures that the yadnya ceremony proceeds smoothly without any disturbances at the niskala level. The movement of scattering yellow rice symbolizes communication, containing the meaning of offering sesajen to evil spirits to prevent them from disturbing humans. The Sidakarya mask dance movement is supported by the properties carried by the Sidakarya mask dancers while dancing, which contain meanings and symbols of communication believed by Hindus as facilitators of the yadnya ceremony.